2011
DOI: 10.1111/j.1740-8261.2011.01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contrast Medium Injection Duration on Peak Enhancement and Time to Peak Enhancement of Canine Pulmonary Arteries

Abstract: Our goal was to investigate the effect of contrast medium injection duration on pulmonary artery peak enhancement and time to peak enhancement. Fourteen dogs were allocated into one of seven predefined weight categories, each category contained two dogs. Dogs in each weight category were assigned to group A or B. Animals in each group received a different contrast medium injection protocol. In group A, a fixed injection rate of 5 ml/s was used. In group B, the contrast injection rate was calculated as follows:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
(86 reference statements)
0
21
0
1
Order By: Relevance
“…U ntil recently, CT applications for the thorax were mostly limited to morphologic evaluation of the chest wall, mediastinum, vessels, and lung parenchyma for differentiating normal from pathological conditions in companion animals . With the increased availability of multidetector‐row CT (MDCT) scanners with up to 320 detector rows that allow image acquisition with high temporal and spatial resolution, the utilization of this modality will likely rise for evaluating the thoracic cardiovascular system in companion animals and has been used in initial case reports and studies …”
Section: Introductionmentioning
confidence: 99%
“…U ntil recently, CT applications for the thorax were mostly limited to morphologic evaluation of the chest wall, mediastinum, vessels, and lung parenchyma for differentiating normal from pathological conditions in companion animals . With the increased availability of multidetector‐row CT (MDCT) scanners with up to 320 detector rows that allow image acquisition with high temporal and spatial resolution, the utilization of this modality will likely rise for evaluating the thoracic cardiovascular system in companion animals and has been used in initial case reports and studies …”
Section: Introductionmentioning
confidence: 99%
“…17 With adjusted injection rates, injection durations tend to be longer producing enhancement profiles that are delayed and broader (i.e., last longer), thereby decreasing the likelihood of missing arterial enhancement at the scanned arterial phase. 9 With both techniques, there was no statistically significant difference in attenuation between ipsilateral renal arteries and veins at the scanned arterial phase. With the timing-bolus technique, this is likely due to the lack of arterial enhancement due to delayed arrival of contrast material in three of the nine patients.…”
Section: Discussionmentioning
confidence: 93%
“…The blood recirculation visibly enhanced with contrast medium may contribute to the overall pattern of contrast enhancement obtained during CT image acquisition. 8 When contrast medium is injected at a constant rate for a prolonged versus brief period, freshly injected contrast medium and recirculating contrast medium already dispersed through the body mix and accumulate, resulting in a more gradual increase in aortic enhancement with time. Without this recirculation, the TAC for aortic contrast enhancement would consist of a rapid increase followed by a uniform, steady-state plateau with a flat, broad peak as the rate of contrast medium clearance from the central blood compartment equilibrates with the injection rate of contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…11 In veterinary medicine, a few CT protocols have been evaluated for contrast enhancement of the caudal vena cava, abdominal aorta, and pulmonary artery. 8,10 However, to the authors' knowledge, a protocol for performing cardiac CT angiography has not been reported for veterinary species. A method is needed to help discriminate intraand extracardiac structures in dogs better than is achieved with echocardiography.…”
Section: Humentioning
confidence: 95%
See 1 more Smart Citation